2001
DOI: 10.1258/0956462011923228
|View full text |Cite
|
Sign up to set email alerts
|

Severe lactic acidosis and thiamine administration in an HIV-infected patient on HAART

Abstract: Severe lactic acidosis has been increasingly reported as a potentially fatal complication of HIV treatment. We report on an asymptomatic HIV-infected woman treated with stavudine, lamivudine and indinavir for one year. She was hospitalized because of progressive dispnoea, oedema, cyanosis and severe lactic acidosis. Arterial blood pH was 6.98, bicarbonate 4.4 mmol/l (normal value 22-26), blood lactate: 29.7 mmol/l (normal value <2.2). Hepatic function was normal. She had an impressively rapid response (within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…101,109 Investigations are ongoing into agents directed at improving mitochondrial function such as riboflavin, thiamine, and L-carnitine. [110][111][112] As with biguanide-associated LA, RRT decisions should be individualized based on metabolic circumstances.…”
Section: Nrtismentioning
confidence: 99%
“…101,109 Investigations are ongoing into agents directed at improving mitochondrial function such as riboflavin, thiamine, and L-carnitine. [110][111][112] As with biguanide-associated LA, RRT decisions should be individualized based on metabolic circumstances.…”
Section: Nrtismentioning
confidence: 99%
“…[1][2][3]6,9,10 Lactic acid levels of 3.6 to 31.2 mmol/L have been documented, which are extremely high compared with the normal range of 0.6 to 2.1 mmol/L. Plasma levels of riboflavin or thiamin were recorded in only one case, where thiamin was normal (827 pg/mL; normal, 211 to 911) and riboflavin was low (6 nmol/L; normal, 6.2 to 39).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…One describes a 39-year-old woman with progressive dyspnea, edema, and cyanosis. 9 Her HAART regimen included stavudine, lamivudine, and indinavir. She had metabolic acidosis, an elevated aspartate transaminase (AST) level, and a blood lactic acid of 29.7 mmol/L.…”
Section: Thiamin Therapymentioning
confidence: 99%
“…Although there are no studies proving the benefit of these substances in NRTIinduced lactic acidosis and despite the lack of beneficial effects in one experimental study [56], a few published case reports suggest that they may be useful in some cases [46,[57][58][59][60][61][62][63]. In a review of published cases we found that administration of specific therapy with cofactors was associated with a significantly lower mortality in patients with lactic acidosis [8].…”
Section: Coadjuvant Agentsmentioning
confidence: 99%